The Role of Product Type in Online Review Generation and Perception: Implications for Consumer Decision-Making - Hang Dong; Keeyeon Ki-cheon Park; Jong Min Kim (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
Product type plays a critical role in shaping how consumers generate, perceive, and utilize online reviews in decision-making. While previous studies have examined various review features, this study highlights the distinct effects of product classification—search goods, experience goods, and credence goods—on both review generation and perceived helpfulness. Drawing on Product Classification Theory, as well as Self-Determination Theory and the Theory of Planned Behavior, we analyze how review characteristics such as text length and photo inclusion vary across product types and influence consumer perceptions. Using a large-scale dataset of verified Amazon reviews, we find that consumers are more likely to produce longer and more visually rich reviews for search and experience goods than for credence goods, which are harder to evaluate and, thus, elicit less elaborate content. In terms of review helpfulness, reviews for experience goods are rated as more helpful than those for credence goods, while those for search goods are seen as less helpful. Furthermore, review length significantly boosts helpfulness for search goods, while photo inclusion enhances it for experience goods. These findings contribute to review effectiveness research by emphasizing the moderating role of product type and offering actionable insights for e-commerce platforms to improve review design and consumer decision-making.